An annotated list of the reptiles of the highland grassland of Tandilia Mountains, Argentina - Vera, David Gustavo (2021)
The study of biodiversity is a fundamental step to develop conservation strategies. Reptile populations are immersed in a global crisis, due to anthropic disturbances. Almost the entire Pampa ecoregion in Argentina was modified for agricultural and livestock activities, the only remnants of mountain native grasslands in Buenos Aires province being the Tandilia and Ventania mountain systems. Ventania reptiles have been exhaustively researched in last years, while Tandilia counts with fewer studies. We presented an actualized reptiles list of the Tandilia Mountain System. We used five data sources to collect presence records: literature, fieldwork, museum collection, citizen science, and a online database. The composition of reptiles from the Tandilia Mountain range includes 26 species in 12 families. Due to the presence of several endemic reptiles, and the representativeness of more than half of the reptiles of Pampa Ecoregion, Tandilia would be useful to determine conservation priority areas to conserve the native grassland and their reptile fauna.